ANTARA TRADISI DAN MODERNITAS: ANALISIS PERBANDINGAN PENDIDIKAN KARAKTER INDONESIA, INGGRIS, JEPANG DAN MALAYSIA - Zilfa, Rohil (Institut PTIQ Jakarta, 2023)
This study aims to explore the implementation of character education in four countries: Indonesia, Japan, Malaysia, and the United Kingdom. Each country has a different approach to shaping students' character, influenced by cultural factors, policies, and education systems. The study used a descriptive qualitative method to explore the literature and policies on character education in each country. The results showed that in Japan, character education is centered on the family with the philosophy of